Advantages of poultry meat for consumers - Strashynskyi, Igor; Marynin, Andriy; Polishchuk, Iryna; Baida , Yana (My University, 2023)
Today, further strides are being made in improving the healthiness of processed poultry products; in particular, offering products with reduced salt, nitrites, and fat. For example, the sodium concentration in chicken nuggets (i.e., sodium chloride required for extracting the salt-soluble proteins from the meat to facilitate binding/gelation during cooking) can be reduced to some extent by partially replacing with potassium/calcium chloride without affecting consumer acceptance.
Keywords: кафедра технології м’яса і м’ясних продуктів; poultry meat; consumer; м'ясо птиці; споживач; перероблене м'ясо птиці